Image of «美人鱼 / Mermaid» in Russian and Chinese Traditions: General and Special - Y. Zhou (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
The results of a comparative analysis of Russian and Chinese myths and legends about the mermaid are presented. Novelty of research consists in the fact that in the current research a comparative analysis of the image of such aquatic creatures in different cultural traditions is presented only to a small extent. Material of the analyses are the texts that contain mention of the mermaids and describe their appearance. The information is given about the origin of the image of a mermaid and a word mermaid . It is reported that in the Chinese records there are a lot of variations of this aquatic image, which can be separated into three main types: “Japanese Cryptobranchidae”, “sea monster” and “the mermaid tribe”. It is noted that third kind of them is closer to the image of a mermaid, which is known today, - the image of a young girl, living in the water (river, lake), who attracts to herself and has the gift to charm. The author points out that many known Chinese stories about the snake and the dragon can to some extent be considered the stories about the mermaid, because in Chinese myths and legends the fish, the snake and the dragon are associated with the water element, and these three images can be transformed into each other. Thus, the comparative analysis showed that there are more differences than similarities in Russian and Chinese mythological texts about the mermaid. They are explained by religious, socio-cultural factors, the difference of mentalities and the overall civilizational features of two cultures - China and Russia.